The Relationship between Transformational Leadership Elements and Employee Attitudes: A Study of Indonesian Startups - Leonardo Thenov; Vanessa Ellivia (Journal of Strategic Innovation and Business Management, 2025)
The relationship of transformational leadership (individual consideration and intellectual stimulation) on employee attitudes (job performance, organizational commitment, self-efficacy, and job involvement) are investigated in this study. This study includes 311 participants from different startups categories such as food & beverages, agriculture, retail, service, and manufacture. Data is collected using Google Forms and evaluated using multiple linear regression. Findings showed that different elements of individual consideration and intellectual stimulation have particularly various effects on employees’ attitudes. The results of this study will be valuable to startups or companies which adopt individual consideration and intellectual stimulation as their variables to understand employees better and to create a manager training program that aligns with the findings.